A SHARP SCHWARZ AND CARATHEODORY INEQUALITY ON THE BOUNDARY - Ornek, Bulent Nafi (Korean Mathematical Soc, 2014)
In this paper, a boundary version of the Schwarz and Caratheodory inequality are investigated. New inequalities of the Caratheodorys inequality and Schwarz lemma at boundary are obtained by taking into account zeros of f(z) function which are di*erent from zero. The sharpness of these inequalities is also proved.
Keywords: Schwarz lemma on the boundary; holomorphic function; JuliaWolf-Lemma